Beyond D-luciferin: Expanding the Scope of Bioluminescence Imaging in vivo - Adams, Spencer T. (2014)
The light-emitting chemical reaction catalyzed by the enzyme firefly luciferase is widely used for noninvasive imaging in live mice. However, photon emission from the luciferase is critically dependent on the chemical properties of its substrate, D-luciferin. In this review, we describe recent work to replace the natural luciferase substrate with synthetic analogs that extend the scope of bioluminescence imaging.